The application of immune stimulators for vaccination of pigs against Swine erysipelas (Erysipelas suum) - Щербакова, Н. С. (Scientific Progress & Innovations, 2012)
Some vaccines do not cause when applying the proper immune response. It depends on the level of resistance which can change from many things, including the age of the animals, feeding conditions, effect of chemical, physical, biological and other factors on the body as well. To enhance the immune response of the body and to correct immune status of the animals, biogenic stimulators are applied. Biogenic stimulators modify metabolic and energetic processes in the body and promote enzymes. The studies on the potential using of biogenic stimulators for vaccination of pigs against Swine erysipelas by means of inactivated vaccines were done. It was ascertained that the application of these drugs in the vaccination of animals enhances erythropoiesis, the number of B-and T-lymphocytes and furthermore promotes phagocytic activity.